Annotated record of the detailed examination of Mn deposits from DSDP Site 66, Leg 7 (Cores 66-4, 66-6, 66-9, 66-10, 66A-3, 66A-5) - Winterer, Edward L; Riedel, William R; Moberly, Ralph; Resig, Johanna M; Kroenke, Loren W; Gealy, E L; Heath, G Ross; Bronnimann, P; Martini, E; Worsley, Thomas R (Supplement to: Winterer, EL et al. (1971): Site 66. In: Winterer, E.L.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, VII, 725-819, https://doi.org/10.2973/dsdp.proc.7.108.1971, 1971)
One of the principal objectives in the Central Pacific Basin was to elucidate the Paleobathymetric history of the region, which is located amidst groups of atolls and guyots that have subsided as much as 2 kilometers since mid-Cretaceous times. After failure to penetrate the entire sedimentary section and to sample basement at Site 65, on the west side of the Central Basin another site in the Basin where basement rocks might be sampled was searched. Likely places were known from unpublished reflection profiles on the east side of the Basin near the Line Islands by the Hawaii Institute of Geophysics. Finally it was decided to drill a transparent section once again in this area acoiding turbidites formations.